2010
DOI: 10.1111/j.1740-8261.2010.01711.x
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Variations in Morphology of the Canine Atlas in Dogs With and Without Atlantoaxial Subluxation

Abstract: Computed tomography images of 120 dogs were reviewed to characterize variations in atlas morphology, and to identify breed-specific morphologic features. The neural arch of the atlas was thicker in large dogs and male dogs than in small dogs, having a layer of trabecular bone between the inner and outer layers of compact bone. The transverse processes of the atlas were relatively longer in large dogs than in small dogs. Twelve (10%) dogs had incomplete ossification of the atlas. Incomplete ossification of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
50
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 8 publications
5
50
1
1
Order By: Relevance
“…Furthermore, the atlantoaxial joint has been associated with several malformations affecting solely the dens but not the joint itself or the screw path area . Also, the CT scan study of the canine atlas identified proportionate dimensions of the atlas transverse process length and the lateral diameter of the vertebral canal in dogs, which supports the hypothesis in our match sized population.…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, the atlantoaxial joint has been associated with several malformations affecting solely the dens but not the joint itself or the screw path area . Also, the CT scan study of the canine atlas identified proportionate dimensions of the atlas transverse process length and the lateral diameter of the vertebral canal in dogs, which supports the hypothesis in our match sized population.…”
Section: Discussionsupporting
confidence: 84%
“…To our knowledge this is the first description of an affected rabbit. Dorsal arch partial aplasia of C1 is also recognised in humans and dogs and has a suspected congenital aetiology (Currarino et al 1994, Owen et al 2008, Warren-Smith et al 2009, Parry et al 2010, Wrzosek et al 2014, Voorbij et al 2015. A congenital aetiology also seems to be the most likely explanation in our rabbit.…”
Section: Discussionmentioning
confidence: 57%
“…Dogs without atlanto‐axial subluxation showed no clinical signs of a lesion in the cervical spinal cord ( Parry et al . ). In five dogs minor trauma or increased physical activity caused the initiation of clinical signs ( Owen et al .…”
Section: Discussionmentioning
confidence: 97%
“…However, our control sample was selected for breeds known to be affected with AAI to limit any breed or size inconsistencies that could alter the established measurement protocol. This was an important distinction from the McLear and Saunders study design because established differences in atlantoaxial structures have been found in affected and nonaffected AAI toy breed dogs compared with other breeds …”
Section: Discussionmentioning
confidence: 99%